Design and Evaluation of a Web-Based Geographic Information System for PPDB Promotion Zoning Based on Student-Origin Distributions - Riko Muhammad Suri; Ahmad Risman; Sidik Praptomo (Universitas Nurul Jadid, 2025)
Advances in information technology have accelerated the digitalization of educational services, including Indonesia’s student admission process (PPDB). This study designs and evaluates a web-based Geographic Information System (GIS) to map student-origin distributions and construct promotion zones that guide PPDB outreach strategies. The system was built with CodeIgniter and Leaflet for interactive mapping, while applicant addresses/school origins were processed via geocoding. Outputs include point maps, density heatmaps, administrative-area aggregation (urban village/sub-district), and simple distance buffers (e.g., 1–3 km) to derive rule-based priority promotion zones (thresholds on density and proximity to the school). Evaluation comprised functional testing (black box) and user assessments using questionnaires (Likert/SUS). Results indicate that the system expedites registration, reduces the risk of data loss, simplifies data summarization, and provides promotion-zoning maps that help committees target outreach more effectively. The contributions are: (1) a PPDB web-GIS model that combines origin mapping with rule-based promotion zoning, (2) a replicable operational workflow, and (3) recommendations for future work, including advanced analytics dashboards and automated notifications